(untitled) (Research, Society and Development, 2024)
Introduction: congenital syphilis is an infection caused by treponema pallidum, which is transmitted from mother to fetus through the placenta. This condition has serious consequences for the newborn. Approximately 1 million pregnant women with syphilis are identified annually in brazil. Objective: to analyze the prevalence of congenital syphilis in brazil. Methodology: a descriptive epidemiological study was done based on data from the department of informatics of the unified health system (datasus) from may 2014 to may 2023. The variations found included: hospital admissions, mortality rates, deaths, hospital costs, age group, color/race, sex, and macro-regions of the country. Results: between 2014 and 2024, there were 652,712 pediatric hospitalizations for asthma in brazil, and the highest hospitalization number: was in 2013. The south region had higher hospitalization rates, while the north region stood out for its significant impact on death numbers. The most affected age group was under 1 year old, with a predominance of females and mixed-race ethnicity. Conclusion: when considering the broad biopsychosocial, economic, and clinical impact caused by congenital syphilis, it is necessary to implement public policies that prioritize early diagnosis and efficient treatment for pregnant women with syphilis.